Functionalized multi-walled carbon nanotube-copper oxide composite nanofluid phase change cold storage material and preparation method thereof
Patent Information
- Application Number
- CN202610692735.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-19
- Publication Date
- 2026-08-28
AI Technical Summary
[0005]为了解决现有水基纳米流体蓄冷材料在长期循环中分散稳定性差、无法同时实现高效导热增强与低过冷度,以及蓄能密度损失过大的技术问题,本发明提供了一种具有高分散稳定性、高导热、低过冷度且能合理保持蓄能密度的功能化多壁碳纳米管-氧化铜复合纳米流体相变蓄冷材料及其制备方法
[0014]1、优异的长期分散稳定性:在最优配比下,本发明制备的纳米流体在静置60天后,其Zeta电位绝对值仍高达33.5 mV(高于30 mV即属高稳定体系),平均粒径仅增长至401.7nm,远超同类产品,确保性能长期可靠。
Smart Images

Figure CN122648056A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a phase change cold storage material, specifically to a composite nanofluid phase change cold storage material based on water, functionalized multi-walled carbon nanotubes and copper oxide nanoparticles, and its preparation method. Background Technology
[0002] With the continued growth of global cooling demand, energy consumption and carbon emissions are becoming increasingly prominent issues. Utilizing phase change materials (PCMs) for cold energy storage is a key technology for balancing energy supply and demand and improving the efficiency of refrigeration systems. Among these materials, water is considered an ideal cold energy storage PCM due to its extremely high latent heat of phase change, non-toxicity, non-flammability, and low cost.
[0003] However, water faces two major bottlenecks in practical applications as a cold storage material: severe supercooling: pure water often needs to be supercooled to below -20°C to freeze during static cooling, leading to increased energy consumption and difficulty in temperature control of the refrigeration system. Low thermal conductivity: water has a low thermal conductivity (approximately 0.6 W / m·K), resulting in slow cold storage and release rates, affecting the system's response speed.
[0004] To address these issues, existing technologies typically involve adding a single type of nanoparticle, such as CuO or carbon nanotubes, to the water. CuO acts as a nucleating agent to reduce supercooling, while carbon nanotubes enhance thermal conductivity. However, single-nanofluids generally suffer from poor long-term dispersion stability. Due to their high surface energy, nanoparticles are prone to aggregation and sedimentation, leading not only to a decline in thermal conductivity enhancement over time but also potential blockage of system piping. While adding surfactants can provide short-term improvement, excessive use can affect fluid properties and lead to failure during long-term thermal cycling. Furthermore, adding nanoparticles dilutes the effective energy storage medium, resulting in a decrease in the overall latent heat of phase change and energy storage density. Therefore, existing technologies struggle to achieve a balance between improving thermal conductivity, suppressing supercooling, and maintaining high energy storage density. Summary of the Invention
[0005] To address the technical problems of existing water-based nanofluid cold storage materials, such as poor dispersion stability during long-term cycling, inability to simultaneously achieve high thermal conductivity enhancement and low undercooling, and excessive energy storage density loss, this invention provides a functionalized multi-walled carbon nanotube-copper oxide composite nanofluid phase change cold storage material with high dispersion stability, high thermal conductivity, low undercooling, and the ability to reasonably maintain energy storage density, as well as its preparation method.
[0006] The objective of this invention is achieved through the following technical solution:
[0007] A functionalized multi-walled carbon nanotube-copper oxide composite nanofluid phase change cold storage material is composed of 99.8~99.9 wt.% base liquid, 0.05~0.15 wt.% nano-additives, and 0.02~0.1 wt.% surfactant, wherein: the base liquid is purified water; the nano-additives are composed of carboxylated multi-walled carbon nanotubes (COOH-MWCNTs) and copper oxide (CuO) nanoparticles, with a mass ratio of COOH-MWCNTs to CuO of 2~8:2~8; and the surfactant is gum arabic (GA), sodium dodecylbenzenesulfonate (SDBS), hexadecyltrimethylammonium bromide (CTAB), or polyvinylpyrrolidone (PVP).
[0008] A method for preparing the above-mentioned functionalized multi-walled carbon nanotube-copper oxide composite nanofluid phase change cold storage material includes the following steps:
[0009] Step 1: Prepare surfactant solution: Add surfactant to base liquid and stir magnetically to obtain a uniform surfactant solution. Control the stirring speed of magnetic stirring at 500~1000 rpm for 30~60 minutes.
[0010] Step 2: Mixing nanoparticles: Add COOH-MWCNTs and CuO nanoparticles to the solution obtained in Step 1, and continue magnetic stirring to obtain a premixed solution. Control the magnetic stirring speed at 500~1000 rpm and the time at 30~60 minutes.
[0011] Step 3, Dispersion treatment: The premixed liquid obtained in Step 2 is subjected to water bath ultrasonic dispersion treatment, followed by probe ultrasonic dispersion treatment. The ultrasonic dispersion temperature is controlled below 40℃ and the frequency is 20~60 kHz; the ultrasonic dispersion frequency is 10~30 kHz.
[0012] Step 4: Collect the finished product: After letting the dispersion obtained in Step 3 stand for 0.5 to 15 days, take the upper stable suspension, which is the composite nanofluid phase change cold storage material.
[0013] Compared with existing single nanofluid cold storage technologies, the present invention has the following significant advantages:
[0014] 1. Excellent long-term dispersion stability: Under the optimal ratio, the nanofluid prepared by this invention still has an absolute value of 33.5 mV for 60 days after standing (above 30 mV is considered a highly stable system), and the average particle size only increases to 401.7 nm, which is far superior to similar products, ensuring long-term reliable performance.
[0015] 2. Significantly enhanced thermal conductivity: The thermal conductivity reaches 0.6377 W / (m·K) at room temperature, which is 6.3% higher than that of pure water (about 0.6 W / (m·K)). It also shows the fastest temperature rise rate in actual melting experiments, which can effectively shorten the energy storage / release time.
[0016] 3. Significantly suppresses supercooling: The freezing start temperature is significantly increased from -20.55℃ for pure water to -11.75℃, and the supercooling is reduced by about 8.8℃. This allows the refrigeration system to start the freezing process without deep supercooling, thus saving energy.
[0017] 4. Optimized comprehensive energy storage performance: Although the energy storage density is reasonably reduced by about 7.2% compared to pure water (440.58 J / g) to 408.85 J / g due to the addition of nanoparticles, the present invention achieves the best balance of performance by greatly improving the heat transfer rate and nucleation performance (dynamic performance) while maximizing the preservation of the static cold storage capacity of the material through the optimal composition ratio. Attached Figure Description
[0018] Figure 1 Flowchart for the preparation of functionalized multi-walled carbon nanotube-copper oxide composite nanofluid phase change cold storage material;
[0019] Figure 2 Zeta potential and particle size;
[0020] Figure 3 Thermal conductivity;
[0021] Figure 4 Energy storage density;
[0022] Figure 5 Images obtained using a transmission electron microscope (TEM).
[0023] Figure 6 Infrared thermal imaging of the melting process. Detailed Implementation
[0024] The technical solution of the present invention will be further described below with reference to the accompanying drawings, but it is not limited thereto. Any modifications or equivalent substitutions to the technical solution of the present invention that do not depart from the spirit and scope of the technical solution of the present invention should be covered within the protection scope of the present invention.
[0025] This invention provides a nanofluid phase change cold storage material (NFPCM) composed of functionalized multi-walled carbon nanotubes (COOH-MWCNTs) and copper oxide (CuO). This material forms a stable heterogeneous structure by constructing coordination bonds between COOH-MWCNTs and CuO, thereby generating a synergistic effect. This composite nanofluid phase change cold storage material consists of a base liquid, nano-additives, and surfactants. By total mass, the base liquid is purified water with a mass fraction of 99.8–99.9 wt.%; the nano-additives have a total concentration of 0.05–0.15 wt.% and are composed of carboxylated multi-walled carbon nanotubes (COOH-MWCNTs) and copper oxide (CuO) nanoparticles, with a COOH-MWCNTs to CuO mass ratio of 2–8:2–8; the surfactants are gum arabic (GA), SDBS, CTAB, or PVP, with a mass fraction of 0.02–0.1 wt.%. Figure 1 As shown, the specific preparation steps are as follows:
[0026] Step 1: Prepare surfactant solution: Add surfactant to base liquid and stir magnetically to obtain a uniform surfactant solution. Control the stirring speed of magnetic stirring at 500~1000 rpm for 30~60 minutes.
[0027] Step 2: Mixing nanoparticles: Add COOH-MWCNTs and CuO nanoparticles to the solution obtained in Step 1, and continue magnetic stirring to obtain a premixed solution. Control the magnetic stirring speed at 500~1000 rpm and the time at 30~60 minutes.
[0028] Step 3, Dispersion treatment: The premixed liquid obtained in Step 2 is subjected to water bath ultrasonic dispersion treatment, followed by probe ultrasonic dispersion treatment. The ultrasonic dispersion temperature is controlled below 40℃ and the frequency is 20~60 kHz; the ultrasonic dispersion frequency is 10~30 kHz.
[0029] Step 4: Collect the finished product: After letting the dispersion obtained in Step 3 stand for 0.5 to 15 days, take the upper stable suspension, which is the composite nanofluid phase change cold storage material.
[0030] Mechanism of Action: The key to this invention lies in the coordination reaction between the -COOH functional groups on the surface of COOH-MWCNTs and the Cu²⁺ ions on the surface of CuO nanoparticles, forming stable Cu-OC chemical bonds. This chemical bonding is not a simple physical mixing, but rather the construction of a three-dimensional heterogeneous structure with "carbon nanotubes as the framework and CuO as the nodes." This structure brings about a triple synergistic effect: First, the high thermal conductivity of carbon nanotubes constructs an efficient thermal transport network; second, the surface-loaded CuO nanoparticles provide abundant heterogeneous nucleation sites, effectively suppressing supercooling; finally, the nanoparticles are tightly bound to the carbon nanotubes through chemical bonds, and with the steric hindrance of GA, the aggregation and sedimentation of the nanomaterials are greatly prevented, achieving ultra-long-term stable dispersion.
[0031] Example 1 (Optimal Ratio):
[0032] Ingredients: Using an analytical balance with an accuracy of 0.1 mg, weigh 99.85 g of purified water (Wahaha), 0.05 g of gum arabic, 0.06 g of COOH-MWCNTs (Aladdin, outer diameter 4~6 nm, length 10~20 µm) and 0.04 g of CuO nanoparticles (Aladdin, particle size <50 nm).
[0033] Preparation: 0.05 g GA was added to 99.85 g water and magnetically stirred at 500 rpm for 30 minutes until dissolved. Then, 0.06 g COOH-MWCNTs and 0.04 g CuO were simultaneously added to the above solution, and stirring was continued for 30 minutes to form a premix. The premix was placed in a water bath sonicator and ultrasonically dispersed at 40 kHz and below 40 °C for 60 minutes. Subsequently, it was further dispersed using a probe sonicator at 20 kHz for 30 minutes, during which the sample temperature was controlled to avoid overheating.
[0034] Post-processing: After sonication, the dispersion was allowed to stand for 24 hours. The very small amount of sediment at the bottom was discarded, and the uniform and stable black suspension at the top was collected to obtain the highly stable composite nanofluid phase change cold storage material H2.
[0035] Example 2:
[0036] The difference between this embodiment and Embodiment 1 is that the mass ratio of COOH-MWCNTs to CuO is 4:1 (H1), 1:1 (H3), 2:3 (H4), and 1:4 (H5).
[0037] Comparative Example 1 (Single CuO Nanofluid C1):
[0038] The preparation method is the same as in Example 1, except that COOH-MWCNTs are not added and the total amount of nano-additives is adjusted to 0.1g of CuO.
[0039] Comparative Example 2 (Single COOH-MWCNTs Nanofluid M1):
[0040] The preparation method is the same as in Example 1, except that CuO is not added and the total amount of nano-additives is adjusted to 0.1g of COOH-MWCNTs.
[0041] Performance test comparison: The performance of Example 1 (H2) was compared with that of Comparative Example 1 (C1), Comparative Example 2 (M1) and pure water.
[0042] The performance test results are shown in Table 1, the specific material composition is shown in Table 2, the DSC analysis is shown in Table 3, and the zeta potential and particle size are shown in Table 4. Figure 2 As shown, the thermal conductivity is as follows Figure 3 As shown, the energy storage density is as follows Figure 4 As shown, with the total addition amount fixed at 0.1 wt.%, the ratio of H2 (0.06 wt.% COOH-MWCNTs + 0.04 wt.% CuO) achieves the optimal solution for stability and thermal conductivity by constructing a stable heterostructure.
[0043] 1. Key findings: H2 is the optimal formulation, achieving the best synergistic effect (Table 1).
[0044] Comparative experiments showed that H2 performed best in several key indicators. This is due to the stable heterostructure constructed by COOH-MWCNTs and Cu. This structure allows CuO to be uniformly distributed on the carbon nanotubes, preventing the aggregation of both while leveraging the advantages of complementary morphologies. Figure 5 ).
[0045] 2. Stability conclusion: The synergistic effect is significant, with H2 showing the best performance. Figure 2 )
[0046] The Zeta potential was the highest and most stable: H2's initial Zeta potential reached -40.4 mV, and remained at -33.5 mV after 60 days (absolute value >30 mV, classifying it as "highly stable"). In contrast, the single-component C1 and M1 decreased to -18.9 mV and -27.8 mV, respectively, after 60 days. Particle size growth was minimal: the average particle size of H2 increased only from 302.7 nm to 401.7 nm over 60 days. In contrast, M1 (pure carbon nanotubes) experienced a dramatic increase in particle size to 2234.9 nm due to entanglement. This demonstrates that the heterostructure effectively suppressed aggregation.
[0047] 3. Conclusion on thermal conductivity and dynamic performance: H2 constructs the most efficient thermal conductivity network. Figure 3 )
[0048] H2 exhibits a thermal conductivity of 0.6377 W / (m·K), 6.3% higher than pure water, the highest among all samples. This is because its stable heterogeneous structure forms a three-dimensional thermally conductive network with carbon nanotubes as the framework and CuO as the connection points. In the infrared thermal imaging melting experiment, H2 consistently showed the highest surface temperature at the same time point, indicating that it indeed converts faster heat conduction into a faster melting rate. Figure 6 ).
[0049] 4. DSC data and conclusions on supercooling: Supercooling was significantly suppressed, but latent heat decreased slightly (Table 3).
[0050] The supercooling was significantly reduced: the freezing initiation temperature of pure water was as low as -20.55℃, while that of H2 was significantly increased to -11.75℃, a reduction of 8.8℃ in supercooling. This indicates that the heterostructure of H2 is a highly efficient nucleating agent.
[0051] Slight decrease in latent heat: Although the latent heats of melting and solidification of H2 (296.2 J / g and 265.1 J / g) are lower than those of pure water, they are not much different from those of other samples, indicating that it can still maintain a high level of heat storage capacity while enhancing thermal conductivity and nucleation.
[0052] 5. Energy Storage Density Conclusion: The cost of improved dynamic performance reflects the trade-offs in the design. Figure 4 )
[0053] H2 exhibits excellent thermal conductivity and nucleation properties, resulting in the highest effective mass fraction of nanoparticles without phase transition capability within the system. This leads to the most significant decrease in energy storage density—from 440.58 J / g in pure water to 408.85 J / g. This provides a core trade-off for material design: to achieve optimal thermal conductivity and undercooling suppression, an energy storage capacity loss of approximately 7.2% must be accepted.
[0054] Table 1
[0055]
[0056] Table 2
[0057]
[0058] Table 3
[0059]
Claims
1. A functionalized multi-walled carbon nanotube-copper oxide composite nanofluid phase change cold storage material, characterized in that... The composite nanofluid phase change cold storage material is composed of 99.8~99.9 wt.% base liquid, 0.05~0.15 wt.% nano-additives and 0.02~0.1 wt.% surfactant, wherein the nano-additives are composed of carboxylated multi-walled carbon nanotubes and copper oxide nanoparticles, and the mass ratio of carboxylated multi-walled carbon nanotubes to copper oxide nanoparticles is 2~8:2~8.
2. The functionalized multi-walled carbon nanotube-copper oxide composite nanofluid phase change cold storage material according to claim 1, characterized in that... The base liquid is purified water.
3. The functionalized multi-walled carbon nanotube-copper oxide composite nanofluid phase change cold storage material according to claim 1, characterized in that... The surfactant is gum arabic, sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium bromide, or polyvinylpyrrolidone.
4. The functionalized multi-walled carbon nanotube-copper oxide composite nanofluid phase change cold storage material according to claim 1, characterized in that... The mass ratio of the carboxylated multi-walled carbon nanotubes to copper oxide nanoparticles is 4:1, 3:2, 1:1, 2:3, or 1:
4.
5. A method for preparing the functionalized multi-walled carbon nanotube-copper oxide composite nanofluid phase change cold storage material according to any one of claims 1-4, characterized in that... The method includes the following steps: Step 1: Prepare the surfactant solution: Add the surfactant to the base liquid and stir magnetically to obtain a homogeneous surfactant solution; Step 2: Mixing nanoparticles: Add COOH-MWCNTs and CuO nanoparticles to the solution obtained in Step 1, and continue magnetic stirring to obtain a premixed solution; Step 3, Dispersion treatment: The premixed liquid obtained in step 2 is subjected to water bath ultrasonic dispersion treatment, and then probe ultrasonic dispersion treatment. Step 4: Collect the finished product: After the dispersion obtained in Step 3 is allowed to stand, take the upper stable suspension, which is the composite nanofluid phase change cold storage material.
6. The preparation method of the functionalized multi-walled carbon nanotube-copper oxide composite nanofluid phase change cold storage material according to claim 5, characterized in that... In step one, the magnetic stirring speed is controlled at 500~1000 rpm, and the time is 30~60 minutes.
7. The preparation method of the functionalized multi-walled carbon nanotube-copper oxide composite nanofluid phase change cold storage material according to claim 5, characterized in that... In step two, the magnetic stirring speed is controlled at 500~1000 rpm, and the time is 30~60 minutes.
8. The preparation method of the functionalized multi-walled carbon nanotube-copper oxide composite nanofluid phase change cold storage material according to claim 5, characterized in that... In step three, the temperature of ultrasonic dispersion is controlled to be below 40°C, and the frequency is 20~60 kHz; the frequency of ultrasonic dispersion is 10~30 kHz.
9. The preparation method of the functionalized multi-walled carbon nanotube-copper oxide composite nanofluid phase change cold storage material according to claim 5, characterized in that... In step four, the settling time is controlled to be 0.5 to 15 days.